KESEIMBANGAN AIR DAN HARA DI HUTAN TANAMAN EUCALYPTUS PELLITA F.Muell MELALUI PENDEKATAN MODEL DINAMIK - , AGUNG BUDI SUPANGAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Forest plantation development in Indonesia still has many obstacles, one of which related to issue stating that forest land degradation and environmental problems affected drought and decreasing soil fertility. The environmental issues associated with the use of short rotation plants (fast growing species) are allegedly going to drain the nutrients and water for their rapid growth. Information related to these environmental issues is rare. It is mainly caused by the focus is still on the wood productivity. The aim of the research was to determine the characteristics of water and nutrients in the E. pellita F.Muell plantation forest. Its objectives were: 1) to study the behavior of the hydrologic cycle in E. pellita forest ecosystem